MANAJEMEN INOVASI KURIKULUM BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 PESERTA DIDIK - Riya Septi; Akhmad Ramli; Bahrani Bahrani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of information and communication technology in the digital era has fundamentally transformed the landscape of education. Conventional curricula that emphasize memorization and teacher-centered learning are no longer sufficient to meet the demands of the 21st century. This study aims to examine how curriculum innovation management based on Project Based Learning (PjBL) can serve as an effective strategy to enhance students’ 21st century skills. Employing a literature review method, the research synthesizes theories and findings from previous studies related to curriculum innovation, educational management, and PjBL. The results indicate that PjBL consistently improves critical thinking, creativity, collaboration, and communication skills, while also fostering character and citizenship. Furthermore, effective curriculum management—including planning, organizing, implementation, and evaluation—emerges as a decisive factor in ensuring the sustainability of PjBL practices. The integration of digital technology and supportive educational policies further strengthens the effectiveness of PjBL within the framework of the Merdeka Curriculum. This study concludes that curriculum innovation management through PjBL is not only a pedagogical strategy but also a transformative approach to preparing students for global challenges and realizing the vision of Indonesia Emas 2045.